Trust in Social Commerce: A Bibliometric Analysis of Live Endorsement and Social Proof in the TikTok Shop Era - Jati, Hafidz Mahkota; Wijaya, Tony; Utama, Agung (Economic and Business Horizon, 2026)
The rapid growth of digital platforms has transformed social commerce into a key channel for online consumer engagement and transactions. This study aims to provide a comprehensive bibliometric review of the evolution of social commerce research, with a focus on trust, live endorsement, and social proof. Through the analysis of 106 Scopus publications (2013-2025) using VOSviewer, this study maps the network of keywords, author collaboration, and joint citations. The results showed that Business (27.9%), Computer Science (24.2%), and Social Sciences (14.6%) were the dominant disciplines. Geographically, Malaysia, China, and the United States are the main contributors. The cluster analysis identified five key themes, including Platform and Adoption, Social Proof, and Quality of Interaction. The study confirms a significant research gap: core topics such as trust and live streaming commerce are identified as still isolated from the main literature networks. These findings provide practical and theoretical implications by highlighting the need for more integrated research frameworks and encouraging practitioners to shift their strategic focus from purchase intention to actual sales conversion.